Regulation and Deregulation in Colombia: Much Ado About Nothing? A Historical Perspective of Regulation - Rudolf Hommes (Inter-American Development Bank, Office of the Chief Economist, 1996)
This paper first offers a historical perspective of regulation, the early steps of Colombian industry and the way it grew. The environment was not conducive to the application of legislation that attempted to regulate monopoly or oligopoly, much less to regulate economic power. A discussion of the modern private sector follows the history.
Keywords: 330